2020
DOI: 10.14444/7027
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Melorheostosis: A Rare Cause for Thoracic Radiculopathy

Abstract: Background: Symptomatic spinal melorheostosis is a rare entity, and its surgical management is even rarer. Our objective is to highlight the importance of considering spinal melorheostosis among the differential diagnosis of thoracic radiculopathy.Methods: We report a case of melorheostosis involving the T9 vertebra presenting with unilateral radicular pain managed surgically by decompression and posterior stabilization.Results: Our patient had complete symptomatic relief following surgical resection without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There are 6 reported cases of surgical treatment of spinal melorheostosis 15 . In these patients, because of the symptoms of myelopathy or radiculopathy, spinal fusion surgery was performed in addition to decompression in 4 of them while only decompression was performed in 2 of them, and the results of surgical treatment were reported to be satisfactory in cases where conservative treatment failed 15 . Recurrence was reported in only 1 of the patients who underwent surgical treatment, and it was reported that decompression was applied again because of neurological worsening 16 .…”
Section: Discussionmentioning
confidence: 99%
“…There are 6 reported cases of surgical treatment of spinal melorheostosis 15 . In these patients, because of the symptoms of myelopathy or radiculopathy, spinal fusion surgery was performed in addition to decompression in 4 of them while only decompression was performed in 2 of them, and the results of surgical treatment were reported to be satisfactory in cases where conservative treatment failed 15 . Recurrence was reported in only 1 of the patients who underwent surgical treatment, and it was reported that decompression was applied again because of neurological worsening 16 .…”
Section: Discussionmentioning
confidence: 99%
“…7 8 Cases with myelopathic symptoms secondary to the spinal cord or nerve root compression by hyperostotic bone in melorheostosis have been reported. 9 10 11 12 13 14 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above symptoms, some patients also have root compression. However, separate nerve root stimulation is rarely observed [ 6 ]. Once the spinal cord is compressed by TOLF, the conservative treatment effect is poor, and surgery is the only effective method.…”
Section: Introductionmentioning
confidence: 99%